Psychoeducation and In Vivo Desensitization Techniques to Reduce Separation Anxiety in Children - Zafirah Hanna Qaddura; Hamidah Hamidah (Guidena)
Separation anxiety is a common thing in children. Still, if the intensity and impact of the anxiety shown begin to interfere with the adaptive functions of the child and parents, and intervention process is needed to overcome the child's anxiety condition. The intervention process that can be carried out is psychoeducation and the application of in vivo desensitization techniques. This study aimed to examine the effectiveness of psychoeducation and in vivo desensitization techniques to reduce separation anxiety in children. This study uses a single case subject A-B method with a follow-up design. The participant in this study was a boy aged 6 years 9 months who experienced separation anxiety. This research was conducted in 6 sessions and lasted for 60 minutes each session. The results showed that psychoeducational techniques and in vivo desensitization could reduce the frequency of behaviors that indicate anxiety in children with separation anxiety.